5.6 The Control of Hypertension In Pregnancy Study (CHIPS) randomised controlled trial. (9th June 2014) - Magee, LA; von Dadelszen, P; Rey, E; Ross, S; Asztalos, E; Murphy, K; Menzies, JM; Sanchez, J; Singer, J; Gafni, A; Gruslin, A; Hutton, E; et al.
Abstract : Background: Most obstetricians believe that BP normalisation in pregnancy reduces maternal complications, but may increase adverse perinatal outcomes. No adequately powered trials of differential BP control have been performed. Objective: Determine best management of non-severe pregnancy hypertension. Methods: In an open pragmatic international multicentre trial, women at 14 +0 –33 +6 wk gestation with non-proteinuric pre-existing or gestational hypertension, office diastolic blood pressure (dBP) 90–105 mmHg (or 85–105 mmHg if on antihypertensives) and a live fetus were randomised to 'less tight' (target dBP 100 mmHg) or 'tight' control (target dBP 85 mmHg). The composite primary outcome was pregnancy loss or high level neonatal care for >48 h in the first 28d of life, and the secondary one/more serious maternal complications before 6wks. Outcomes were compared between groups using logistic regression adjusted for key prognostic factors (alpha = 0.05, two-sided, intention-to-treat). Results: Of 1030 women randomised, 987 (94 sites) were included in the analysis. 74.6% had pre-existing hypertension. Women in 'less tight' (n=497) [vs. 'tight' (n = 490)] control had higher mean dBP by 4.5 mmHg (95% CI 3.6, 5.4), but similar rates of the primary (perinatal) outcome [31.4% vs. 30.7%; aOR 1.03, 95% CI 0.78, 1.36] and secondary (maternal) outcome [3.7% vs. 2.0%; aOR 1.74, 95% CI 0.79, 3.84]. Women receiving 'less tight' control more frequently developed BP ≥160/110mmHg) (40.4% vs. 27.5%; aOR 1.78, 95% CI 1.35, 2.36). Interpretation: 'Tight' control is safer for the mother. These data reassure that it has no adverse effects for the baby. A target dBP of 85mmHg should be aimed for. Funding: Canadian Institutes of Health Research.